Genealogy of instruments for prodrome evaluation of psychosis - Daneault, Jean-Gabriel; Stip, Emmanuel (Frontiers in Psychiatry, 2013)
Objective: Over the last fifteen years, researchers from around the world have developed instruments for assessing the risk of conversion to psychosis. The objective of this article is to review the literature on these instruments by focusing on genealogy links and on their performance in predicting conversion to psychosis. Method: A systematic review of articles published since 1980 relating to risk assessment instruments for conversion to psychosis by manual search and consultation of electronic databases MEDLINE, EMBASE and PsycINFO. Results: Three hundred and ninety one (391) publications were selected and analyzed. Among these, 22 instruments were identified. These instruments are briefly described and placed on a timeline according to their year of publication. A code of positions, patterns and forms is used to schematize the characteristics of each instrument. A table is presented to show changes in rates of conversion to psychosis within cohorts of subjects considered at risk according to the instruments. A second code of shades and outlines is used to schematize the characteristics of each cohort of patients. The two graphics set the stage for a discussion about the major strategies that were adopted to improve the performance of risk assessment instruments. Conclusions: These graphics allow a better understanding of the origin, evolution, current status, strengths, shortcomings and future prospects of research on risk assessment instruments.